A Case of Prepubertal Ovarian Tissue Cryopreservation in Metachronous Bilateral Mature Ovarian Teratoma Requiring Bilateral Oophorectomy - Malik, Tom; Wheeler, Robert; Hall, Nigel J.; Gray, Juliet (European Journal of Pediatric Surgery Reports, 2022)
Mature ovarian teratoma has the potential to occur metachronously in the contralateral ovary. There are significant implications for fertility as bilateral oophorectomy may be indicated. In prepubertal girls, ovarian tissue cryopreservation (OTC) offers the only possibility of a future biological pregnancy but outcome data are limited. We present a case of prepubertal OTC in a 12-year-old girl undergoing a second oophorectomy for metachronous contralateral mature teratoma. We offer a discussion of the challenges that emerged regarding perioperative decision-making, balancing the need for safe oncological resection with the desire to preserve fertility.
Keywords: mature teratoma; dermoid cyst; ovarian tumor; ovarian tissue cryopreservation; fertility